The Efficacy of Madeira Vine Leaf Extract Combined with Turmeric Rhizome Extract Gel Topically on Second-Degree Burn Wound in Albino Rats - Hisyam, Mirza Atikah Madarina; Yuniarti, Wiwik Misaco; Theresia, Sis Wisnuarti; Yudaniayanti, Ira Sari; Lukiswanto, Bambang Sektiari; Sudjarwo, Sri Agus; Widiyatno, Thomas Valentinus (Universitas Airlangga, 2023)
Burns is now considered one of the most destructive forms of trauma affecting humans and animals. This study aimed to determine the effect of Madeira vine leaf extract combined with 2% Turmeric rhizome extract (MVLTR) gel administered topically on second-degree burn wound in albino rats based on the number of fibroblasts. A total of 25 male rats weighed 200–300 grams were divided into five groups i.e. (C-) was normal skin, (C+) was burn and treated using 1% silver sulfadiazine, (T1) was burn and treated using 1.25% MVLTR gel, (T2) was burn and treated using 2.5% MVLTR gel, and (T3) was burn and treated using 5% MVLTR gel. The burn wound was performed on the right gluteus of rats, and the therapy was applied twice a day topically, starting after the burn wounds were made. Skin samples were collected on day 15. The histopathological examination was performed by counting fibroblast cells and then analyzed using One-way ANOVA, continued with the Duncan test. Based on the results showed that the C- group was significantly different compared to C+, T1, T2, and T3 groups. C+ had a significant difference with the T1 and T3 groups, meanwhile not significantly different from the T2 group. T2 was not significantly different from the C+ and T3 groups. In conclusion, MVLTR gel at 5% concentration has the potential to be an effective treatment for second-degree burns, as indicated by the increased number of fibroblasts.